Palliating inside the lines: The effects of borders and boundaries on palliative care in rural Canada. (November 2016) - Giesbrecht, Melissa; Crooks, Valorie A.; Castleden, Heather; Schuurman, Nadine; Skinner, Mark; Williams, Allison
Abstract: We draw lines to divide our world into specific places, territories, and categories. Although borders and boundaries are dynamic and socially constructed, their existence creates many broad impacts on our lives by geographically distinguishing between groups (e.g., us/them; here/there; inside/outside) at various scales from the national down to the personal spaces of the individual. Particularly, borders and boundaries can be used to define a variety of differing spaces such as the familial, social, economic, political, as well as issues of access – including access to health services. Despite the implicit connection between borders, boundaries, and health, little research has investigated this connection from a health geography perspective. As such, this secondary thematic analysis contributes to addressing this notable gap by examining how borders and boundaries are experienced and perceived to impact access to palliative care in rural Canada from the perspectives of the formal and informal providers of such care. Drawing upon data from qualitative interviews ( n  = 40) with formal and informal palliative caregivers residing in four different rural Canadian communities, five forms of borders and boundaries were found to directly impact care delivery/receipt: political; jurisdictional; geographical; professional; and cultural. Implicitly and explicitly, participants discussed these borders and boundaries while sharing their experiences of providing palliative care in rural Canada. We conclude by discussing the implications of our findings for palliative care in rural Canada, while also emphasizing the need for more health geography, and related social science, researchers to recognize the significance of borders and boundaries in relation to health and healthcare delivery. Lastly, we emphasize the transferability of these findings to other health sectors, geographical settings, and disciplines. Highlights: Contributes new insight regarding how borders/boundaries are connected to healthcare. Provides experiential perspectives on how borders/boundaries shape rural palliative care. Identifies implications for palliative care in rural Canada. Offers a new 'lens' for others to examine links between health and borders/boundaries.